IMPACT OF HERBICIDES WITH DIFFERENT CONCENTRATIONS OF FOLIAR NUTRIENTS OF TWO RICE VARIETIES YIELDS - Al-Ziady, Saddam; Musa, A.; Hadi, A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigates effect of herbicides and foliar nutrients of rice varieties yields (Anbar and Yasamin ). A field experiment was carried out at the rice research station at Al-Mishkhab, Najaf during two seasons 2020 and 2021. Factorial experiment Randomized Complete Block Design was used with 3 within replicates. Combinations included two rice varieties (12), with four weeding treatments (H1, H2, weed-free and control without weed control) with two concentrations of nano fertilizer (F1:21 g L-1 and F2:10.5 g L-1) as well as normal fertilization. The results showed that V1H4F3 had a significant superiority in reducing the density and the dry weight of the weeds, which gave the lowest value 84.3 and 82.0 plant m-2 and 101.0 and 123.0 g m-2 for the two seasons, respectively. Variety V2 achieved the highest values the grain yield. of (V2H3F3) which reached 5.43 and 5.31 ton h-1 for the two seasons. The herbicide of H2 gave the lowest weed density of 27.3 and 22.3 g m-2 for the two seasons, respectively. It is concluded that the variety V1 is better into tolerating to the weeds competition.